Malaria complicada por Plasmodium ovale en Salamanca, España - María Paz Vaquero-Herrero; Jesús Martín Centellas; Verónica Temprado Moreno; Hugo Guillermo Ternavasio-de la Vega (Sociedade Galega de Medicina Interna, 2020)
Background: Monomicrobial imported infection by Plasmodium ovale is very rare. Case presentation: We report a case of complicated imported malaria by Plasmodium ovale in a man who suffered from subacute recurrent fever, thrombocytopenia and splenomegaly. Conclusion: Both the patient history and a search of epidemiological medical history were fundamental for confirming the suspicion.